The Influence of Animated Film Media on the Social Behaviour of 5-6 Year Old Children at RA An-Nida - Dea Surabina Br Tarigan; Khadijah Khadijah (Edumaspul: Jurnal Pendidikan, 2024)
Emotional social development is very important to a person because human beings are essentially social beings and interrelated with each other. In social development, children are expected to be able to maintain good friendship and to form sensitivity to their surroundings. Through the animation the child can see or learn a lot of new things so that the child often imitates or exemplifies the same acts as what he sees in the show. This research is done at RA An Nida with a kind of experimental research, using an approach. The population was 17 children and they were sampled all using a saturated sample (Sugiono,2021). Conclusion Based on the results of the investigation that has been carried out about the influence of the animated media film “Riiko The Series” it can be concluded that the media animated film “ Riiko the Series” proved to have an influence on the social behavior of children aged 5-6 years in RA AnNida. The results showed the influence of animated film media on the social behavior of 5-6-year-olds in RA An-Nida.